Performance of Tablet Splitters, Crushers, and Grinders in Relation to Personalised Medication with Tablets - Herman J. Woerdenbag; J. Carolina Visser; Marlyn P. A. M. Leferink op Reinink; Roël R. van Orsoy; Anko C. Eissens; Paul Hagedoorn; Hilda Dijkstra; Derk P. Allersma; Shi W. Ng; Oscar S. N. M. Smeets; Henderik W. Frijlink (Pharmaceutics, 2022)
Swallowing problems and the required dose adaptations needed to obtain optimal pharmacotherapy may be a hurdle in the use of tablets in daily clinical practice. Tablet splitting, crushing, or grinding is often applied to personalise medication, especially for the elderly and children. In this study, the performance of different types of (commercially available) devices was studied. Included were splitters, screwcap crushers, manual grinders, and electric grinders. Unscored tablets without active ingredient were prepared, with a diameter of 9 and 13 mm and a hardness of 100–220 N. Tablets were split into two parts and the difference in weight was measured. The time needed to pulverise the tablets (crush time) was recorded. The residue remaining in the device (loss) was measured. The powder was sieved to obtain a particle fraction >600 µm and <600 µm. The median particle size and particle size distribution of the later fraction were determined using laser diffraction analysis. Splitting tablets into two equal parts appeared to be difficult with the devices tested. Most screwcap grinders yielded a coarse powder containing larger chunks. Manual and especially electric grinders produced a finer powder, making it suitable for administration via an enteral feeding tube as well as for use in individualised preparations such as capsules. In conclusion, for domestic and incidental use, a screwcap crusher may provide sufficient size reduction, while for the more demanding regular use in hospitals and nursing residences, a manual or electric grinder is preferred.